PEMANFAATAN LAHAN PASCA TAMBANG BATUBARA SEBAGAI USAHA PETERNAKAN SAPI POTONG BERKELANJUTAN - Taufan Purwokusumaning Daru; Henny Pagoray; Suhardi Suhardi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The purpose of this study was to assess the sustainability of the system through the development of a sustainability index in beef cattle farm in coal post mining land. The study conducted in the coal mining company at Kutai regency. The method used was descriptive through case studies. The technique is done by purposive sampling based on the number of beef cattle reared in the post-mining land. Analysis of beef cattle cultivation used basis multidimensional scaling (MDS) based on the dimensions of the ecological, economic, social and cultural. Each attribute has a score. Furthermore, the score of each attribute dimensional analyzed to determine one or several points that reflect the position of the sustainability of the beef cattle farm systems. Through this MDS sustainability point position can be visualized. Sustainability index has a scale interval of 0 to 100. If the index value of more than 50 categorized sustainable and is less than 50 was not sustainable. The results of  ecological dimensions index was 55.56, economic dimension index was 66.67, and  sustainable index for social dimension was 72.73. If sustainability index value on the range of 50.00 – 75.00 was on the category of fair sustainable.  In order to utilization of coal post mining land can be cultivated by beef cattle.